1999
DOI: 10.1093/pubmed/21.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Statin prescribing in Nottingham general practices: a cross-sectional study

Abstract: General practices with high deprivation indices serve more deprived populations with a higher prevalence of cardiovascular disease, and may be assumed to have a greater need for statins. Despite this, practices with higher deprivation indices prescribed fewer statins to their patients than less deprived practices. It was not possible to identify whether the more deprived general practices had successfully identified at risk individuals but it is likely that special efforts are needed to increase the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…280 Practices with higher levels of socio-economic deprivation had significantly lower levels of statin prescribing per 1000 population aged 35-69 years. This relationship persisted when adjustment was made for the level of fibrate prescribing, and was highly significant (p < 0.0001).…”
Section: Equity Issues Variation In Prescribing Relating To Socio-ecomentioning
confidence: 95%
See 1 more Smart Citation
“…280 Practices with higher levels of socio-economic deprivation had significantly lower levels of statin prescribing per 1000 population aged 35-69 years. This relationship persisted when adjustment was made for the level of fibrate prescribing, and was highly significant (p < 0.0001).…”
Section: Equity Issues Variation In Prescribing Relating To Socio-ecomentioning
confidence: 95%
“…This relationship persisted when adjustment was made for the level of fibrate prescribing, and was highly significant (p < 0.0001). 280 However, this relationship is no longer so evident. Following the introduction of national and local guidelines, Packham found that, in 1997 and 1998, statin prescribing rates increased, with proportionally larger increases among practices in more deprived areas, so that no significant relationship was found between deprivation and prescribing rates.…”
Section: Equity Issues Variation In Prescribing Relating To Socio-ecomentioning
confidence: 99%
“…Statins are effective lipid-lowering agents that inhibit 3-hydroxy-3-methylglutaryl CoA reductase (HMGCR) by binding directly to it and thereby reduce endogenous cholesterol synthesis. There is substantial variability in interindividual response to statin therapy for cardiovascular disease (2)(3)(4), and pharmacogenetic differences are thought to contribute significantly to this variability (5)(6)(7)(8)(9)(10). Genetic analyses of subjects from the Pravastatin Inflammation CRP Evaluation (PRINCE), Cholesterol and Pharmacogenetics (CAP), Pravastatin or Atorvastatin Evaluation and Infection Therapy-Thrombolysis in Myocardial Infarction 22 (PROVE IT- TIMI 22), and other cardiovascular riskreduction clinical trials showed that pharmacogenetic variants in HMGCR and KIF6 influence the degree of lipid reduction during statin therapy (5,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a growing body of research that has highlighted large variations in overall prescribing rates between GP practices, which are only partially explained by factors other than healthcare need. [15][16][17][18][19] Prescribing of statins has increased significantly in recent years, [20][21][22] although the use of statins in patients with a history of CHD remains well below recommended levels. 20 23 Statin prescribing has been shown to vary between health authorities and GPs 21 22 24 25 and between patients on the basis of gender, demographics, and deprivation.…”
mentioning
confidence: 99%